To solve the system of equations, we can use the method of substitution or elimination. Let's use the method of elimination.
First, let's multiply the second equation by 4 to make the coefficients of x equal:
28x - 12y = 196
Now, we can subtract this equation from the first equation to eliminate x:
(4x + 7y) - (28x - 12y) = -33 - 196
Combine like terms:
-24x + 19y = -229
Now, we have a new equation:
-24x + 19y = -229
Next, let's multiply the first equation by 3 to make the coefficients of y equal:
12x + 21y = -99
Now, we can subtract this equation from the second equation to eliminate y:
(7x - 3y) - (12x + 21y) = 49 - (-99)
Combine like terms:
-5x - 24y = 148
Now, we have a new equation:
-5x - 24y = 148
We now have a system of two equations:
-24x + 19y = -229
-5x - 24y = 148
Now, let's solve this system using the method of elimination.
First, let's multiply the second equation by -24 to make the coefficients of y equal:
120x + 576y = -3552
Now, we can add this equation to the first equation to eliminate y:
(-24x + 19y) + (120x + 576y) = -229 + (-3552)
Combine like terms:
96x + 595y = -3781
Now, we have a new equation:
96x + 595y = -3781
Finally, we can multiply the first equation by 595 and the second equation by 19 to make the coefficients of x equal:
-5656x - 4521y = 541395
-95x - 4560y = 2812
Now, we can add these equations to eliminate x:
(-5656x - 4521y) + (-95x - 4560y) = 541395 + 2812
Combine like terms:
-5751x - 9081y = 544207
Now, we have a new equation:
-5751x - 9081y = 544207
Now, we have a system of two equations:
96x + 595y = -3781
-5751x - 9081y = 544207
We can solve this system of equations using various methods, such as substitution or elimination. Let me know if you would like me to show you how to solve this system using a different method.
4x + 7y = -33
7x - 3y = 49
What is the solution for the system of equations above?
1 answer